Kawasan Wisata Budaya di Pulau Lakkang Kota Makassar - Nurul Maghfirah (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2023)
The potential for cultural tourism on Lakkang Island can be divided into two, including physical and non-physical. The physical remains of six Japanese bunkers that are tens of years old, traditional houses of local residents and a bamboo forest of approximately one hectare in area. While non-physical in the form of traditional dances (Mala dance, Bugis dance, Paduppa dance, Fan and Uncle dance), events (annual folk parties, National photographer jamboree competition in 2016, jamboree held by the P3E Unit Waste Bank, and bamboo craft workshops which was exhibited at the Makassar International Eight Festival and Forum 2018). A significant increase in tourists also occurred from year to year by 24.1% and 6.7%. Therefore, this potential must be supported by adequate facilities and infrastructure that are in accordance with the potential on Lakkang Island. The purpose of this writing is to meet the standard needs of infrastructure facilities that are in accordance with the potential of the Lakkang Island tourist area. The conceptual approach used is the traditional Bugis Makassar architectural concept approach combined with bamboo materials which are widely available on Lakkang Island. The method to achieve the goal is by synthesis analysis. Where the data obtained is analyzed and then synthesized and then used as a design reference. The results of this study are in the form of a concept of the appearance of infrastructure buildings that can be transformed into physical designs.